Latin America Climate-Smart Villages AR4D sites: 2019 Inventory - Bonilla Findji, Osana; Martínez Barón, Deissy; López, Claudia; Álvarez, Osman; Ortega, Luis Alberto; Paz, Liliana Patricia; Castellanos, Andrea; Álvarez Toro, Patricia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Inventory of CSA practices evaluated and/or implemented across Latin America’s Climate-Smart Villages in 2019.